2015
DOI: 10.1111/ntwe.12051
|View full text |Cite
|
Sign up to set email alerts
|

I didn't feel like I was alone anymore’: evaluating self‐organised employee coping practices conducted via Facebook

Abstract: This document is the author's final accepted version of the journal article. There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it. 'I didn't feel like I was alone anymore': Evaluating selforganised employee coping practices conducted via Facebook AbstractThe long-term fracturing of the labour movement has led to increased attention to employee coping practices under new management practices and labour processes.H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 44 publications
(122 reference statements)
1
39
0
2
Order By: Relevance
“…Characterisations of the contradictory or paradoxical implications of constant connectivity include opposites such as positive/negative, liberating/dominating and autonomy enhancing/autonomy limiting (Mazmanian et al ., ; in the case of smartphones). Similarly, the blurring of public and private boundaries presents employers with new social media(ted) tensions, for instance, between allowing employees to voice opinions and protecting organisational reputations (Cohen and Richards, ; McDonald and Thompson, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Characterisations of the contradictory or paradoxical implications of constant connectivity include opposites such as positive/negative, liberating/dominating and autonomy enhancing/autonomy limiting (Mazmanian et al ., ; in the case of smartphones). Similarly, the blurring of public and private boundaries presents employers with new social media(ted) tensions, for instance, between allowing employees to voice opinions and protecting organisational reputations (Cohen and Richards, ; McDonald and Thompson, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Critical studies on blogs and closed Internet groups (Cohen and Richards 2015;Ellis and Richards 2009;Richards 2008;Richards and Kosmala 2013;Sayers and Fachira 2015;Schoneboom 2007Schoneboom , 2008Schoneboom , 2011 have shown that workers find the Internet to be a media for collective identification detached from organizational culture. Therefore, we can also imagine that workers are not exchanging emotionologies, but rather following emotionologies of the Internet while defying emotionologies of work.…”
Section: Final Considerationsmentioning
confidence: 97%
“…Sayers and Fachira (2015) analyzed how hairstylists vent about customers in a professional online forum, using humor or tragedy to find solidarity from colleagues in coping with emotional labor. Cohen and Richards (2015) found that closed Facebook groups may provide workers a forum for mutual emotional support.…”
Section: Online Informal Resistancementioning
confidence: 98%
“…Cohen and Richards (2015) Reputation, control over technology and learning opportunities were explanations for involvement in communal resources. Hyman (1999) The history of open source software development has been characterised by resisting curtailments on the 'freedom' of coding through the imposition and exploitation of copyrights by corporations (Rigi, 2013;Stallman, 2002).…”
Section: Collectivising and The Internetmentioning
confidence: 99%
“…Lücking and Pernicka, 2009) and second, to contribute to the growing body of work on virtual spaces as organising forums (e.g. Cohen and Richards, 2015;Upchurch and Grassman, 2015). Unlike other work in the field (e.g.…”
Section: Introductionmentioning
confidence: 99%